Post-exercise voluntary drinking cessation is associated with the normalization of plasma osmolality and thirst perception, but not of urine indicators or net fluid balance - Capitán Jiménez, Catalina (2022)
Post-exercise rehydration has been widely studied, with particular emphasis on retention of ingested fluid; comparatively little research has been done on why we drink more or less. To identify physiological values corresponding to voluntary drinking cessation (VDC), nine males exercised intermittently at 70-80% HRmax in the heat (WBGT= 28.1±0.7°C), to achieve a dehydration of approximately 4.0% body mass (BM). After exercise, participants were instructed to drink water as long and as much as they needed. Urine color (Ucolor), specific gravity (USG), osmolality (Uosm), plasma osmolality (Posm), fullness, BM, and thirst perception (TP) were measured pre- and post-exercise, and at VDC. Each variable was compared for the three points in time with a one-way ANOVA. Participants reached dehydration of -3.6±0.3% BM. Pre-exercise USG (1.022+-0.004) was lower than at VDC (1.029+-0.004) P=0.022; Uosm did not change over time (P=0.217), Ucolor was lower pre-exercise (3.4+-0.7) vs. postexercise (5.5+-1.23) P=0.0008, and vs. VDC (6.3+-1.1) P<0.0001. Posm showed a difference between pre-exercise (289.5+-2.3) and postexercise (297.8+-3.9) p=0.0006, and between postexercise and VDC (287.3+-5.4), p<0.0001. TP postexercise (96.4+-4.34) was significantly higher than pre-exercise (36.2+-19.1) and VDC (25.0+-18.2) p<0.0001. At VDC, participants had re-covered 58.7+-12.1% of BM loss. At the point of voluntary drinking cessation, Posm, and thirst per-ception had returned to their pre-exercise values, while rehydration relative to initial BM was still incomplete.